New strawberry harvesting robot for elevated-trough culture - Feng, Qingchun; Wang, Xiu; Zheng, Wengang; Qiu, Quan; Jiang, Kai (International Journal of Agricultural and Biological Engineering, 2012)
Feng Qingchun*, Wang Xiu, Zheng Wengang, Qiu Quan, Jiang Kai (National Engineering Research Center for Information Technology in Agriculture, Beijing 100097, China) Abstract: In order to improve robotic harvesting and reduce production cost, a harvesting robot system for strawberry on the elevated-trough culture was designed. It was supposed to serve for sightseeing agriculture and technological education. Based on the sonar-camera sensor, an autonomous navigation system of the harvesting robot was built to move along the trough lines independently. The mature fruits were recognized according to the H (Hue) and S (Saturation) color feature and the picking-point were located by the binocular-vision unit. A nondestructive end-effector, used to suck the fruit, hold and cut the fruit-stem, was designed to prevent pericarp damage and disease infection. A joint-type industrial manipulator with six degrees-of-freedom (DOF) was utilized to carry the end-effector. The key points and time steps for the collision-free and rapid motion of manipulator were planned. Experimental results showed that all the 100 mature strawberry targets were recognized automatically in the harvesting test. The success harvesting rate was 86%, and the success harvesting operation cost 31.3 seconds on average, including a single harvest operation of 10 seconds. The average error for fruit location was less than 4.6 mm. Keywords: strawberry harvesting robot, elevated-trough culture, machine vision, nondestructive end-effector, autonomous navigation system, manipulator, sensor DOI: 10.3965/j.ijabe.20120502.001 Citation: Feng Q C, Wang X, Zheng W G, Qiu Q, Jiang K. New strawberry harvesting robot for elevated-trough culture. Int J Agric & Biol Eng, 2012; 5(2): 1